Glucocorticoid administration restores salience network activity in patients with spider phobia. Issue 10 (12th August 2018) - Soravia, Leila Maria; Schwab, Simon; Weber, Nico; Nakataki, Masahito; Wiest, Roland; Strik, Werner; Heinrichs, Markus; de Quervain, Dominique; Federspiel, Andrea
Abstract : Background: Glucocorticoids reduce phobic fear in patients with anxiety disorders. Although the neurobiology of anxiety disorders is not fully understood, convergent structural and functional neuroimaging studies have identified abnormalities in various brain regions, including those in the salience network (SN) and default mode network (DMN). Here, we examine the effects of glucocorticoid administration on SN and DMN activity during the processing of phobic stimuli. Methods: We use functional magnetic resonance imaging to record brain activity in 24 female patients with spider phobia who were administered either 20 mg of cortisol or placebo while viewing pictures of spiders. Fourteen healthy female participants were tested with the same task but without substance administration. Independent component analysis (ICA) performed during stimulus encoding identified the SN and DMN as exhibiting synchronized activation in diverse brain regions; thus, we examined the effects of cortisol on these networks. Furthermore, participants had to rate their level of fear at various time points. Results: Glucocorticoids reduced phobic fear in patients with spider phobia. The ICA performed during stimulus encoding revealed that activity in the SN and DMN was reduced in placebo‐treated patients versus healthy controls. Brain activity in the SN, but not the DMN, was altered in cortisol‐ versus placebo‐treated patients to a level that was similar to that observed in healthy controls. Conclusions: Activity in both the SN and DMN was reduced in patients with spider phobia. Cortisol administration altered the SN activity to a level that was comparable to that found in healthy controls. This alteration in SN activity might reflect the fear‐reducing effects of glucocorticoids in phobia.